2021
DOI: 10.3389/fphar.2021.629379
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits Ferroptosis in Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a subtype of stroke characterized by high mortality and disability rates. To date, the exact etiology of ICH-induced brain injury is still unclear. Moreover, there is no effective treatment to delay or prevent disease progression currently. Increasing evidence suggests that ferroptosis plays a dominant role in the pathogenesis of ICH injury. Baicalin is a main active ingredient of Chinese herbal medicine Scutellaria baicalensis. It has been reported to exhibit neuroprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…More importantly, they reported that 15-HpETE-PE was catalyzed by ALOX15 as a ferroptotic signal in their TBI model [ 19 ]. The pharmacological inhibitor of ALOX15, baicalein, also showed neuroprotective effect in ICH and TBI models [ 41 , 42 ]. In this present study, we revealed that the protein level of ALOX15 started to increase at 24 h after SAH modeling and maintained a high level throughout the whole EBI period.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, they reported that 15-HpETE-PE was catalyzed by ALOX15 as a ferroptotic signal in their TBI model [ 19 ]. The pharmacological inhibitor of ALOX15, baicalein, also showed neuroprotective effect in ICH and TBI models [ 41 , 42 ]. In this present study, we revealed that the protein level of ALOX15 started to increase at 24 h after SAH modeling and maintained a high level throughout the whole EBI period.…”
Section: Discussionmentioning
confidence: 99%
“…Some natural products and traditional Chinese medicine-related content have also been confirmed to improve the prognosis of stroke by regulating ferroptosis. The baicalin, carthamin yellow, dauricine, (−)-epicatechin, kaempferol, and paeonol ameliorate neuronal ferroptosis in vitro or in vivo stroke models via regulating ACSL4, GPX4, TFR1, Fe 2+ , and NRF2 pathways ( Chang et al, 2014 ; Duan et al, 2021 ; Guo et al, 2021 ; Jin Z. L. et al, 2021 ; Peng et al, 2021 ; Yuan et al, 2021 ), which show great potential in the treatment of stroke. Treating MCAO rats with Naotaifang (a traditional Chinese herbal medicine compound) extract involves inhibition of acute cerebral ischemia-induced neuronal ferroptosis and neurobehavioral disorder through TFR1/DMT1 and SCL7A11/GPX4 pathways ( Lan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2011 ), and reduce the pro-apoptotic proteins, Bax and caspase-3 ( Zhang Y. et al, 2015 ). Baicalin reportedly decreased protein expression of NF-κB P65, iNOS, COX-2, and MMP9 ( Xu et al, 2013 ; Liang et al, 2017 ; Chen et al, 2018 ), protected glutamine synthetase from ROS ( Song et al, 2020 ), and inhibited ferroptosis ( Duan et al, 2021 ). Ginsenosides are the main active components of ginseng, and more than 40 different monomer structures have been identified.…”
Section: Discussionmentioning
confidence: 99%